HUBUNGAN KARAKTERISTIK PETANI MANGGA DENGAN LUAS LAHAN DAN PENDAPATANNYA - Elly Rasmikayati; Lucyana Trimo; Bobby Rachmat Saefudin (Agros Journal of Agriculture Science, 2023)
Majalengka has a large area of mango plantations, but farmers' income is still low. The purpose of this study is to describe the area and identify the relationship between land area and the income of mango farmers in Majalengka Regency. This study uses a quantitative research design with primary data analysis, namely the population of mango farmers in Majalengka Regency is 130 people. The data were analyzed using a descriptive statistical approach using a cross tabulation tool and using the chi-squared test through tables. The results showed that there was a relationship between the level of education and the area of land and income of mango farmers.Kewords: mango farmers; land area; farmer’s incomeINTISARI Majalengka memiliki lahan perkebunan mangga yang cukup luas, tetapi pendapatan petani masih rendah. Tujuan dari penelitian ini adalah mendeskripsikan luas dan mengidentifikasikan hubungan luas lahan terhadap pendapatan petani mangga Kabupaten Majalengka. Penelitian ini menggunakan desain penelitian kuantitatif dengan analisis data primer yaitu populasi petani mangga Kabupaten Majalengka sebanyak 130 orang. Data dianalisis menggunakan pendekatan statistika deskriptif dengan alat cross tabulation serta penggunaan chi-squared test melalui tabel. Hasil penelitian menunjukkan bahwa terdapat hubungan yang antara tingkat pendidikan dengan luas lahan dan pendapatan petani mangga.